Risk factors associated with the low birth weight in a health area from Camagüey - Ener de Jesús Fernández Brizuela; Fernando Del Valle Piñera; Lourdes López Labarta (Medisan, 2021)
Introduction: The birth weight is, undoubtedly, the most important variable to determine the possibilities that a new born has experiencing a satisfactory growth and development, so that the rate of new born with low weight is considered nowadays a general indicator of health.